Effects of Short-Term Almonds and Walnuts Intake on Serum Fatty Acid Composition, Metabolic Profile and Adiposity on Obese Adults - Cardona-Alvarado, Mónica I.; Ortega, Francisco J.; Ramírez-Chávez, Enrique; Tejero, María Elizabeth; Molina-Torres, Jorge; Fernández-Real, José M.; Perez-Luque, Elva L. (Disease and Health: Research Developments Vol. 2, 2024)
Background: Obesity has emerged as a serious public health threat in the 21st century. According to the 2016 National Health and Nutrition Survey of the Mexican population, the prevalence of overweight and obesity is 72.5% in adults aged 20 and older. Purpose: The purpose of the study is to evaluate changes in serum fatty acids, metabolic profile and inflammation markers after a dietary intervention of 15g of walnuts and 15g of almonds for 8 weeks in obese subjects. Patients and Methods: A total of 48 sedentary obese grade I subjects (13 men and 35 women) of 30 to 50 years old without evidence of chronic degenerative, infectious, or neoplastic diseases, was studied. Anthropometric measures, body composition, serum glucose, lipid profile, insulin, lipocalina-2, high sensitivity C-reactive protein (hsCRP), adiponectin, and fatty acids profile were analyzed at the baseline and after 8 weeks of dietary intervention. Data normality was tested using the Kolmogorov-Smirnov test. The anthropometric and metabolic data were expressed as the mean ± standard deviation. Differences between groups were examined using the paired t-test. Non-parametric variables were transformed into logarithms. In order to examine the size effect of each anthropometric and metabolic parameter, we used the Cohen d. The statistical significance was set at p<0.05. Results: A significant decrease in all measures of obesity (weight, waist circumference, hip circumference, BMI, and fat mass, p<0.0001) was found. The adiponectin (30.4%, p=0.007), lipocalin-2 concentrations (17.9%, p=0.014), and total polyunsaturated fatty acids (PUFAs) percentage (1.6% p=0.040) significantly increased after intervention, particularly the eicosapentaenoic acid and docosahexaenoic acid percentages were increased marginally. A significant decrease in saturated fatty acids levels (3%, p=0.001), in particular the myristic acid (C:14), and palmitic acid (C:16), in total cholesterol (6.7%, p=0.01), and LDL (11.4%, p=0.002) levels, and in all measures of obesity (weight, waist circumference, hip circumference, BMI and fat mass, p<0.0001) were found. The effect size for the intervention was large for all measures of obesity, and moderate for BMI, adiponectin, palmitic acid, and palmitoleic acid. Conclusion: In conclusion, a significant increase of 30% in adiponectin and LCN2 (17.9%) concentrations were found. Additionally, a significant decrease in all measures of obesity, total cholesterol, and LDL concentrations after the intervention was observed. The SFA percentage significantly decreased, in particular, the myristic acid (C:14), and palmitic acid (C:16). The total PUFAs percentage significantly increased, and particularly the percentages of the eicosapentaenoic acid (EPA, C:20:5 \(ω\)-3) and docosahexaenoic acid (DHA C:22:6 \(ω\)-3) marginally increased. The effect size was large for all measures of obesity, except for BMI as well as for adiponectin which was moderate. Only in baseline, significant positive correlations of total saturated fatty acids, lauric and stearic acids with hsCRP concentration, and Myristic acid with triglycerides were found. This study data show that the consumption of almonds and walnuts for a short time may improve the metabolic state and measures of obesity.